Gamification technology in teaching: Exploring how mathematics teachers make use of Kahoot! Gamification to facilitate learning of probability in classrooms - Mbete, Ayanda (Rhodes University, Faculty of Education, Department of Education)
This study seeks to examine the use of Kahoot! as a gamification technology in practice with Grade six teachers to explore its use in supporting the learning of Probability in Mathematics in rural primary schools. Purposive sampling was adopted wherein nine Grade six mathematics teachers from four rural primary schools in Amathole East district were selected as participants of the study. In addition, to inform this qualitative case study, an interpretive paradigm was adopted. Data was collected using semi-questionnaires, semi-structured interviews, non-participant observations, workshop discussions and reflective journals. The TPACK by Mishra & Koehler (2009) and Vygotsky's (1978) socio-cultural theory were employed as the lenses through which all the proceedings of the study were based. The key findings indicate that integrating Kahoot! gamification technology, in the 'Probability' lesson, has positive consequences such as bringing fun into the classroom, enhancing learner participation, prompt feedback and offering a learner-driven approach to learning as opposed to the conventional teaching strategies. The findings also revealed that enabling and constraining factors are associated with using Kahoot! in teaching: the ICT infrastructure, teachers' competency levels and the environment in which teaching and learning occurs. This study concluded that the use of Kahoot enhances the learning of probability in rural under-resourced primary schools. This study recommended the integration of Kahoot gamification into the mathematics curriculum.
Keywords: Gamification; Kahoot!; Mathematics-- Study and teaching (Elementary) -- South Africa -- Eastern Cape; Probabilities; Educational technology; Rural schools -- South Africa -- Eastern Cape; Technological Pedagogical Content Knowledge; Cultural-historical activity theory